Are Thailand's Mangosteen and Durian Complementary in the Global Market? - Rangkakulnuwat, Poomthan (Universitas Muhammadiyah Yogyakarta, 2024)
Mangosteen is one of Thailand’s major agricultural exports, generating income and employment in the country’s agricultural sector. This research examined whether Thailand’s durian fruit can complement mangosteen in the global market. The country-pair and time-fixed effects of Poisson maximum likelihood were employed in the model, and the estimated results were separated into eight cases. The findings indicate that Thailand’s durian complements mangosteen in the global market. Thai mangosteen exporters are advised to implement high pricing strategies, divide their market into upper-middle-income and high-income nations, and promote durian along with mangosteen. Improving the skill of mangosteen farmers to achieve a higher yield and quality than competitors is an essential factor.